Escargot controls somatic stem cell maintenance through the attenuation of the insulin receptor pathway in Drosophila - Demarco,RS; Stack,BJ; Tang,AM; Voog,J; Sandall,SL; Southall,TD; Brand,AH; Jones,DL (Cell Reports, 2022)
Adult stem cells coordinate intrinsic and extrinsic, local and systemic, cues to maintain the proper balance between self-renewal and differentiation. However, the precise mechanisms stem cells use to integrate these signals remain elusive. Here, we show that Escargot (Esg), a member of the Snail family of transcription factors, regulates the maintenance of somatic cyst stem cells (CySCs) in the Drosophila testis by attenuating the activity of the pro-differentiation insulin receptor (InR) pathway. Esg positively regulates the expression of an antagonist of insulin signaling, ImpL2, while also attenuating the expression of InR. Furthermore, Esg-mediated repression of the InR pathway is required to suppress CySC loss in response to starvation. Given the conservation of Snail-family transcription factors, characterizing the mechanisms by which Esg regulates cell-fate decisions during homeostasis and a decline in nutrient availability is likely to provide insight into the metabolic regulation of stem cell behavior in other tissues and organisms.